Evaluation of lipid profile in patients with thalassemia - Faiz Suwadi Falih Akleh; Haitham Safi Atwan khudir; Zahraa Ahmed jabr ALkabi; Abbas Raheem Abualhail Awadh; Sarah Abbas Abdel Reda Jabouri; Hasanain Okab Oufi Hilal (Genius Journals, 2024)
Thalassemia can be defined as a condition in which a reduced rate of synthesis of one or more of the globin chains leads to imbalanced globin chain synthesis, defective hemoglobin production, and damage to the red cells or their precursors from the effects of the globin subunits that are produced in relative excess. While Lipid abnormalities, including low levels of all fractions of serum lipids, have been repeatedly reported in all phenotypes of B-thalassemia. Unexpectedly, the concentration of total cholesterol, HDL and LDL has been found in B-thalassemia intermedia patients even lower than in thalassemia major, without a clear explanation of pathophysiology of these findings. Accordingly Lipids are necessary to save life of cells because they are important sources of energy. A lipid profile is determination of the level of specific lipids in the blood. Two important lipids, cholesterol and triglycerides, are cycled in the blood by lipoprotein compounds. The lipoprotein particles are measured with a lipid profile. They are divided by their density into high-density lipoproteins , low-density lipoproteins , and very low density lipoproteins. The present study is designed to investigate changes markers of thalassemia patients compared to the control group. Lipid profile examination has shown significant increase in TG levels and significant decrease in all cholesterol forms in patients.
Keywords: Thalassemia; lipid profile; patients